Phonogram (2006), volume 1 ebook Rue britannia (full color edition). - Gillen, Kieron (Phonogram (2006), 2022)
The critically beloved work from the creators of THE WICKED + THE DIVINE. Includes RUE BRITANNIA, THE SINGLES CLUB, and THE IMMATERIAL GIRL, with RUE BRITANNIA newly colored. The world where Music Is Magic has never looked better.